2015
DOI: 10.1111/opn.12083
|View full text |Cite
|
Sign up to set email alerts
|

What are the relative merits of interventions used to reduce the occurrences of disruptive vocalisation in persons with dementia? – a systematic review

Abstract: Triggers which lead to older people with dementia expressing disruptive vocalisation should be identified. Multiple individualised interventions should be used to reduce the occurrences of the disruptive vocalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 44 publications
2
21
0
1
Order By: Relevance
“…The selection process for studies is summarised in Figure 1. Further details of the Namaste Care studies are listed in additional file 3 of Bunn et al 32 With respect to research design, the 86 papers reported: l 17 evidence reviews (not Namaste Care) [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] l 59 papers reporting 51 primary studies (not Namaste Care) l 10 papers reporting 8 Namaste Care studies. 22,27,29,[44][45][46][47][48]50,130 REALIST REVIEW OF NAMASTE CARE AND OTHER MULTISENSORY INTERVENTIONS NIHR Journals Library www.journalslibrary.nihr.ac.uk…”
Section: Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The selection process for studies is summarised in Figure 1. Further details of the Namaste Care studies are listed in additional file 3 of Bunn et al 32 With respect to research design, the 86 papers reported: l 17 evidence reviews (not Namaste Care) [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] l 59 papers reporting 51 primary studies (not Namaste Care) l 10 papers reporting 8 Namaste Care studies. 22,27,29,[44][45][46][47][48]50,130 REALIST REVIEW OF NAMASTE CARE AND OTHER MULTISENSORY INTERVENTIONS NIHR Journals Library www.journalslibrary.nihr.ac.uk…”
Section: Phasementioning
confidence: 99%
“…The evidence suggests that one of the most important aspects of programmes is how they enable meaningful relationships to form between providers and residents who are no longer able to communicate easily with speech and have other symptoms consistent with advanced dementia, for example by having the same person provide each session, by incorporating one-to-one interaction into an activity and by providers having the skills to work with people with advanced dementia. 50,64,77,84,92,96,106,121,123,131 By contrast, interventions involving providers who are unfamiliar to residents and/or do not have the appropriate skills 99,100 or are unable to engage socially with people with dementia may be less effective. 127 Stakeholders at the workshop suggested that having the same person deliver Namaste Care was not always practical and that rather the aim should be to achieve a consistent approach and attitude towards programme delivery:…”
Section: Programme Theorymentioning
confidence: 99%
“…However, these studies showed a limited clinical impact since VB resumed immediately after the intervention (Cohen-Mansfield & Werner, 1997) or the interventions were being underused by staff (von Gunten et al, 2011). Based on a systematic review (n=8) of non-pharmacological interventions for VB, Randall and Clissett (2015) recommended rigorous study of individualized interventions that combine several approaches and that involve training staff to identify the reasons or meanings for the VB.…”
Section: Decrease Vocal Behavioursmentioning
confidence: 99%
“…In light of these findings, a study led to developing an intervention approach based on the meanings of VB in older people living with ND (hereinafter called 'the approach') (Bourbonnais & Lavallée, 2014). As recommended by Bird et al (2009) and Randall and Clissett (2015), this approach sought to optimize the use of nonpharmacological interventions. It describes how to identify the meanings of VB using strategies that lead to decision-making in partnership with family and formal caregivers and how to associate these meanings to multiple individualized interventions.…”
Section: Decrease Vocal Behavioursmentioning
confidence: 99%
See 1 more Smart Citation